Correlation of Fragment Size Distribution and Fracture Surface in Coal Cutting Under Various Conditions - A. Wahab Khair; W. M. Devilder (The National Institute for Occupational Safety and Health (NIOSH), 1988)
"This paper presents an analysis of fragment size distribution and characteristics of fracture surface in coal cutting using a rotary coal cutting simulator. Coal cutting by a drum type continuous miner was simulated in the laboratory. A series of tests along both the face and butt cleat direction of coal under different operating and in-situ conditions were performed. In each experiment the cut surface was photographed microscopically and the coal cuttings were collected and sized. Data were used to show how and to what extent various parameters effect size distribution of the coal cutting and how this correlates with the characteristics of the fracture surface. This study resulted in establishing a number of distinct correlations between the size distribution and fracture surface. These correlations were primarily based on the degree of interaction between adjacent bits and the amount of bit-coal interaction taking place on the cutting path. Some of the major results of this study are as follows:Zones of bit-coal interactions proved vital toward understanding the effect the conical bit has on the fragmentation process. This in turn led to the identification of areas which are responsible for the production of fines and generation of respirable dust.The various parameters employed in the coal cutting experiments which showed a strong effect on the coal fragment size distribution were: bit type, bit spacing, depth of cut, in-situ stresses, and cleat orientation. Bit angle and cutting head velocity exhibited the least effect and no correlation was established.From this study it is obvious that the key to achieving efficient coal fragmentation is to limit the degree of bit-coal interaction that takes place throughout the bit path while causing maximum interaction between adjacent bits. Accomplishing this not only increases the percentage of large fragments produced but limits the amount of secondary crushing that takes place in the bit path thus resulting in decreasing fines and consequently, the amount of respirable dust generated.Over 2,000 continuous mining machines (introduced in the 1950's) equipped with conical bits or point attach bits account for well over half of the United States' production from underground coal mines. Today, competition in the coal industry has increased, due mainly to coal market conditions and legal restrictions, thus placing an emphasis upon increasing production, efficiency and health/safety of the workers. Mine operators are always interested in finding the most efficient performance of continuous mining machinery to produce the largest amount of size of coal at the lowest cost. An increase of fine material sent to the cleaning plant can seriously overload the plant to the extent that plant efficiencies deteriorate significantly (1). Also, the difficulty and expense of cleaning very small particles often cannot be done economically and thus, thousands of tons of coal are sent to the refuse pile because of costly or ineffective cleaning facilities. It has been said, ""the efficient extraction of coal or rock implies breakage into a size range that contains a minimum quantity of very small sizes"" (2). All known fragmentation theories concur that more fragmentation requires more energy (3). So, the importance of reducing fines is already evident from an outlook upon efficiency.Now, let's consider another view point., duet generation."